The gift of speech: why parents implant their children. Issue 6 (3rd July 2017) - Barnet, Belinda
Abstract: In Australia cochlear implantation of profoundly deaf infants, babies, and young children is approaching 100% saturation. Why do parents choose to implant rather than learn Auslan? What is the Deaf community's reaction to this and how will it change Sign as a living language? In this article, the author is a Deaf parent who chose to implant her Deaf child. When she initially published in a news outlet on this topic the reaction was quite heated: how terrible a parent you must be if you are denying your child Sign! This article explains the reasoning behind that decision to implant, taking issue with the notion that giving a child an 'extra ability' of speech means that you do not love them as they are. Nothing is natural, but everything is acquired or augmented – in all children.